2014
DOI: 10.3390/molecules19045325
|View full text |Cite
|
Sign up to set email alerts
|

Rice Bran Feruloylated Oligosaccharides Activate Dendritic Cells via Toll-Like Receptor 2 and 4 Signaling

Abstract: This work presents the effects of feruloylated oligosaccharides (FOs) of rice bran on murine bone marrow-derived dendritic cells (BMDCs) and the potential pathway through which the effects are mediated. We found that FOs induced phenotypic maturation of DCs, as shown by the increased expression of CD40, CD80/CD86 and MHC-I/II molecules. OPEN ACCESS Molecules 2014, 19 5326FOs efficiently induced maturation of DCs generated from C3H/HeN or C57BL/6 mice with normal toll-like receptor 4 (TLR-4) or TLR-2 but not DC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 37 publications
2
21
1
Order By: Relevance
“…In recent studies, we [5] and others [42] have demonstrated that dietary fibers can signal and modulate immune responses via binding to PRRs [5,43,44]. Our data suggest that TLR receptors are also involved in the effects of the currently tested fibers as the immunomodulating capacity was reduced in the presence of a MyD88 inhibitor [5,30,44].…”
Section: Discussionsupporting
confidence: 55%
“…In recent studies, we [5] and others [42] have demonstrated that dietary fibers can signal and modulate immune responses via binding to PRRs [5,43,44]. Our data suggest that TLR receptors are also involved in the effects of the currently tested fibers as the immunomodulating capacity was reduced in the presence of a MyD88 inhibitor [5,30,44].…”
Section: Discussionsupporting
confidence: 55%
“…An increasing number of studies in recent years have proven that various oligosaccharides, including chitosan oligosaccharide, alginate oligosaccharide and rice bran feruloylated oligosaccharide, regulate immune functions via the MAPK pathway 3032 . Our previous results showed that GOS could activate all MAPKs, including p38, JNK and ERK 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies describe an immune modulation by different NDO on cellular level via the interaction with specific sugar receptors including DC-SIGN, TLRs or C type lectin receptors [ 24 , 25 , 33 35 ]. Further studies in our experimental setting are necessary to investigate the role of other types of receptors involved in scGOS/lcFOS-mediated, direct mechanisms on human MoDC.…”
Section: Discussionmentioning
confidence: 99%